2011
DOI: 10.1051/0004-6361/201116721
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-powered chromospheres in classical T Tauri stars

Abstract: Context. Optical spectra of classical T Tauri stars (cTTS) are rich in emission lines of low-excitation species that are composed of narrow and broad components, which indicates the existence of two emitting regions with different kinematics, densities, and temperatures. The photospheric spectrum is often veiled by an excess continuous emission. This veiling is usually attributed to radiation from a heated region beneath the accretion shock. The broad emission lines of H i, He ii, Ca ii, Fe ii, and other speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 64 publications
5
54
0
2
Order By: Relevance
“…The diagram shows the anti-phase variations between stellar and NC velocities, as reported in Paper I, and is similar to what has been observed in several CTTS (e.g. Petrov et al 2001Petrov et al , 2011.…”
Section: Veiling Line Strength and Phasesupporting
confidence: 86%
“…The diagram shows the anti-phase variations between stellar and NC velocities, as reported in Paper I, and is similar to what has been observed in several CTTS (e.g. Petrov et al 2001Petrov et al , 2011.…”
Section: Veiling Line Strength and Phasesupporting
confidence: 86%
“…In DR Tau, an inverse-P Cygni profile is detected in the Paγ and Paδ lines. Such a feature is observed also in the Hδ line while it is absent in the Hα and Hβ lines (Petrov et al 2011, Alencar et al 2001 which, on the contrary, are strongly peaked at red-shifted velocities. The high-n Brackett lines are more symmetric, consistent with their lower optical depth with respect to line emission from lower levels (e.g.…”
Section: Hydrogen Linesmentioning
confidence: 89%
“…Petrov et al (2011) found a smooth change of about 5 km s −1 in the radial velocity of the narrow emission component in the He  5875 Å line from August 14 to 17. This implies a lower limit of the period of about three days.…”
Section: Analysis: the Structure Of The Accretion Flowmentioning
confidence: 91%